Schwannoma of the foot: report of four cases and literature review - Angelini, Andrea; Bevoni, Roberto; Biz, Carlo; Cerchiaro, Maria Chiara; Girolami, Mauro; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Schwannoma is a soft tissue tumor that rarely presents in the foot. Patients are usually asymptomatic, but in some cases symptoms typically result from the mass effect and direct involvement of the nerve and surrounding tissue. We report on four consecutive cases. The first patient was a 57-years-old female that referred symptoms similar to the Morton’s neuroma with a mass arising from the medial plantar nerve. The second patient was treated for a schwannoma in the plantar area. The third case was a female with a schwannoma arising from the sural nerve and the fourth patient had a tumor arising from the medial plantar nerve. All patients underwent surgical excision and histological evaluation. No signs of neurological deficit or recurrence were observed at final follow-up. Purpose of the study was to define clinical features, optimal management and outcome of schwannomas of the foot, through an accurate review of the literature.